Moyamoya Syndrome Associated with Henoch-Schönlein Purpura - SHIARI, Reza; TABATABAEI NODUSHAN, Seyed Mohamad Hossein; MOHEBBI, Mohamad Mahdi; KARIMZADEH, Parvaneh; JAVADZADEH, Mohsen (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Shiari R, Tabatabaei Nodushan SMH, Mohebbi MM, Karimzadeh P, Javadzadeh M. Moyamoya Syndrome Associated with Henoch-Schönlein Purpura. Iran J Child Neurol. Autumn 2016; 10(4):71-74. Abstract Some reports have shown the association between Moyamoya syndrome and autoimmune diseases. Herewith, we present a 3.5 yr old girl with Henoch- Schönleinpurpura (HSP) who was treated with steroids because of sever colicky abdominal pain. However, central nervous system manifestations such as headache, ataxia and vision impairment developed during 6 months of her outpatient follow-up. More evaluation using MRA revealed intracranial stenosis of internal carotid artery and arterial collaterals that were in favor of Moyamoya syndrome. To our knowledge, this is the first report of Moyamoya syndrome following henoch-schönleinpurpura. References 1. Aicardi J. Diseases of the nervous system in childhood, 2nd ed. London: Mac Keith Press, 1998. pp. 554–556. 2. Currie S, Raghavan A, Batty R, Connolly DJ, Griffiths PD. Childhood moyamoya disease and moyamoya syndrome: a pictorial review. Pediatr Neurol 2011; 44:401–13. 3. Suzuki J, Takaku A. Cerebrovascular, “moyamoya” disease. Disease showing abnormal net-like vessels in base of brain. Arch Neurol 1969; 20:288–99. 4. Smith ER, Scott RM. Spontaneous occlusion of the circle of Willis in children: pediatric moyamoya summary with proposed evidence-based practice guidelines. A review. J Neurosurg Pediatr. 2012 Apr;9(4):353-60. 5. Ozen S, Ruperto N, Dillon MJ, Bagga A, Barron K, Davin JC, et al. EULAR/PReS endorsed consensus criteria for the classification of childhood vasculitides. Ann Rheum Dis. 2006; 65(7): 936-941. 6. Gardner-Medwin JM, Dolezolova P, Cummins C, Southwood TR. Incidence of Henoch-Schonleinpurpura, Kawasaki disease, and rare vasculitides in children of different ethnic origins. Lancet. 2002; 360: 1197-1202. 7. Aalberse J, Dolman K, Ramnath G, Periera RR, Davin JC. Henoch-Schönleinpurpura in children: an epidemiological study among Dutch paediatricians on incidence and diagnostic criteria. Ann Rheum Dis. 2007; 66(12): 1648-1650. 8. Saulsbury FT. Henoch-Schönleinpurpura in children. Report of 100 patients and review of the literature. Medicine (Baltimore). 1999; 78(6): 395-409. 9. Tarvin SE, Ballinger S. Henoch-Schonleinpurpura. Current Paediatrics. 2006; 16: 259-263. 10. Cahide Y, Hu¨seyin, Şükrü Arslan C et al. Bilateral brachial plexopathy complicating henoch-schönleinpurpura. Brain & Development 28 (2006) 326–328. 11. Bellman AL, Leicher CR, Moshe SL, Mezey AP. Neurologic manifestations of henoch–schönleinpurpura: Report of three cases and review of the literature. Pediatrics 1985; 75:687-92. 12. Reza Shiari. Neurologic Manifestations of Childhood Rheumatic Diseases. Iran J Child Neurol 2012; 6(4): 1-7. 13. Lee YJ, Yeon GM, Nam SO, Kim SY. Moyamoya syndrome occurred in a girl with an inactive systemic lupus erythematosus. Korean J Pediatr 2013; 56(12): 545–549. 14. Seol HJ, Wang KC, Kim SK, Hwang YS, Kim KJ, Cho BK. Headache in pediatric moyamoya disease: review of 204 consecutive cases. J Neurosurg 2005; 103: Suppl: 439-42. 15. Suzuki J, Kodama N. Moyamoyadisease — a review. Stroke 1983; 14:104-9. 16. Baba T, Houkin K, Kuroda S. Novel epidemiological features of moyamoya disease. J Neurol Neurosurg Psychiatry 2008; 79:900-4. 17. Tanghetti B, Capra R, Giunta F, Marini G, Orlandini A. Moyamoya syndrome in only one of two identical twins: case report. J Neurosurg 1983; 59:1092-4. 18. Guey S, Tournier-Lasserve E, Kossorotoff M. Moyamoya disease and syndromes: from genetics to clinical management. Appl Clin Genet 2015; 8: 49–68. 19. Scott RM, Smith JL, Robertson RL, Madsen JR, Soriano SG, Rockoff MA. Long-term outcome in children with moyamoya syndrome after cranial revascularization by pialsynangiosis. J Neurosurg 2004; 100: Suppl: 142-9. 20. Lubman DI, Pantelis C, Desmond P, Proffitt TM, Velakoulis D. Moyamoya disease in a patient with schizophrenia. J Int Neuropsychol Soc 2003; 9:806-10. 21. Smith ER, Scott RM. Moyamoya Disease and Moyamoya Syndrome. N Engl J Med 2009; 360:1226-37. 22. Research Committee on the Pathology and Treatment of Spontaneous Occlusion of the Circle of Willis. Guidelines for diagnosis and treatment of moyamoya disease Neurol Med Chir (Tokyo) 2012; 52(5):245–266. 23. Fung LW, Thompson D, Ganesan V. Revascularisation surgery for paediatricmoyamoya: a review of the literature. Childs Nerv Syst 2005; 21(5):358–364.